New Prospective Phosphodiesterase Inhibitors: Phosphorylated Oxazole Derivatives in Treatment of Hypertension - Iryna V. Nizhenkovska; Kateryna V. Matskevych; Oksana I. Golovchenko; Oleksandr V. Golovchenko; Antonina D. Kustovska; Mikhaeel Van (Tabriz University of Medical Sciences, 2023)
Purpose: One of the promising chemical groups for the development of new antihypertensive medicines, the action of which is associated with the inhibition of phosphodiesterase III (PDE3) activity, are phosphorylated oxazole derivatives (OVPs). This study aimed to prove experimentally the presence of the OVPs antihypertensive effect associated with decreasing of PDE activity and to justify its molecular mechanism. Methods: An experimental study of the effect of OVPs on phosphodiesterase activity was performed on Wistar rats. Determination of PDE activity was performed by fluorimetric method using umbelliferon in blood serum and organs. The docking method was used to investigate the potential molecular mechanisms of the antihypertensive action of OVPs with PDE3. Results: The introduction of OVP-1 50 mg/kg, as a leader compound, led to the restoration of PDE activity in the aorta, heart and serum of rats with hypertension to the values observed in the intact group. This may indicate the possibility of the development of vasodilating action of OVPs by the influence of the latter on the increase in cGMP synthesis due to inhibition of PDE activity. The calculated results of molecular docking of ligands OVPs to the active site of PDE3 showed that all test compounds have a common type of complexation due to phosphonate groups, piperidine rings, side and terminal phenyl and methylphenyl groups. Conclusion: The analysis of the obtained results both in vivo and in silico showed that phosphorylated oxazole derivatives represent a new platform for further studies as phosphodiesterase III inhibitors with antihypertensive activity.